Pengaruh Kompetensi Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan di PDAM Tirta Boalemo - Eksan, Zoel Manan; Asi, Lisda L.; Podungge, Robiyati (Ikatan Da'i Indonesia, 2025)
This research aims to determine the extent of the influence of Work Competence and Work Motivation on Employee Work Productivity at PDAM Tirta Boalemo. The data collection technique in this study used a questionnaire with a population of all employees of PDAM Tirta Boalemo, totaling 95 employees. The sampling technique used in this study employs saturated sampling due to the relatively small population size. So the sample used in this study consisted of 95 employees.The analytical test tool used in this research is multiple linear regression. The data analysis method uses the SPSS 22 application. Based on the research results of multiple regression analysis tests, it shows that partially Work Competence has an effect on Work Productivity and Work Motivation has an effect on Work Productivity. Meanwhile, simultaneously Work Competence and Work Motivation influence Work Productivity. The results of the coefficient of determination obtained by the R square value show that the Work Productivity variable can be explained by the Work Competence and Work Motivation variables of 42.7% while the remaining 57.3% is influenced by other variables not included in the regression model. Such as Performance, Work Effectiveness, Training and Compensation.